AB0766 Comparing Iphone Compass Application with Inclinometer and Universal Goniometer for the Assessment of Cervical Rotation in Patients with Ankylosing Spondylitis. (9th June 2015) - Kenar, G.; Zengin, B.; Yarkan, H.; Cetin, P.; Sari, I.; Onen, F.; Akkoc, N.
Abstract : Background: Cervical rotation reflects restriction of mobility in axial disease in ankylosing spondylitis (AS) and it can be assessed in several approaches based on the use of either an inclinometer, a goniometer or a tape measure. New generations of smartphones are equipped with a gyroscope and an accelerometer which in combination with a smartphone's operating system or specific software applications can be used for various inclinometric functions. Objectives: The aim of the study was to assess the reliability and validity of using iphone built in compass application, as compared to using inclinometer and universal goniometer in the assessment of cervical rotation patients with AS. Methods: The study sample included 30 AS patients (8 females, 22 males) with a mean age of 46.8 (±12.2). BASMI scores were obtained from patient charts. The mean BASMI score of AS patients was 37.6 (±30.6). Two examiners measured cervical rotation of each patient using iPhone4 compass application and also inclinometer and universal goniometer, twice with each method. A cap with a velcro patch on top and an iphone case with a Velcro patch on the bottom were used to stabilize the iphone's position during measurements. Intra-rater and inter-rater reliability were examined with intra-class correlation coefficients (ICC). The agreements between the methods facing one another, were assessed by Bland-Altman method. Results: We observed an excellent intra and inter-rater reliability in the whole study sample for all three methods (Table 1 and Table 2 ). Bland-Altman analysis showed a good agreement between the iphone and inclinometer methods with a mean difference (bias) of -5.6 for examiner 1 (95% CI -7.6 to -3.6) and -6.3 for examiner 2 (95% CI -8.8 to -3.8). Upper and lower limits of agreement were 4.9 (95% CI 1.4 to 8.3) and -16.2 (95% CI −19.6 to -12.7) for examiner, and 6.6 (95% CI 2.3 to 10.9) and -19.3 (95% CI -23.5 to -15.0) for examiner 2. Mean differences according to Bland-Altman analysis between the iphone and universal goniometer measurements were 2.3 for examiner 1 (95%CI -0.4 to 5.2) and 4.1 for examiner 2; between the universal goniometer and inclinometer were -8.0 for examiner 1 (95% CI -11.2 to -4.8) and -10.4 for examiner 2. Conclusions: IPhone compass application is a simple and accessible way of measuring cervical rotation in patients with AS. Measurements acquired with iphone show excellent intra and inter-rater reliability and a good agreement with inclinometer and universal goniometer, with slightly lower values than obtained with inclinometer, and slightly higher values than with universal goniometer. Disclosure of Interest: None declared